2016
DOI: 10.1080/17451000.2016.1241411
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of Coralliidae with descriptions of new species from New Caledonia and the Hawaiian Archipelago

Abstract: The systematics of Coralliidae has been revised based on molecular phylogenetic analysis and detailed morphological studies. This revision has also revealed the existence of new species. In order to fully accomplish this revision, five new species including Hemicorallium aurantiacum sp. nov., Pleurocorallium bonsaiarborum sp. nov., P. clavatum sp. nov., and P. norfolkicum sp. nov. from New Caledonia, and H. guttatum sp. nov. from the Hawaiian Archipelago are described by integrating the phylogenetic inference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A significant number of collections were also made in the enigmatic octocoral families Plexauridae and Isididae but detailed morphological taxonomic keys for these families in the central and south Pacific are incomplete and require further attention. Recent efforts to revise the taxonomy of families and genera within the Octocorallia have provided significant contributions to our knowledge of deep-water coral diversity in the Pacific Ocean (Tu et al, 2016;Moore et al, 2017;Cairns, 2018). It is likely that as these specimens are more widely scrutinized using both molecular and morphological taxonomic tools, more species identifications can be determined.…”
Section: Noteworthy Observationsmentioning
confidence: 99%
“…A significant number of collections were also made in the enigmatic octocoral families Plexauridae and Isididae but detailed morphological taxonomic keys for these families in the central and south Pacific are incomplete and require further attention. Recent efforts to revise the taxonomy of families and genera within the Octocorallia have provided significant contributions to our knowledge of deep-water coral diversity in the Pacific Ocean (Tu et al, 2016;Moore et al, 2017;Cairns, 2018). It is likely that as these specimens are more widely scrutinized using both molecular and morphological taxonomic tools, more species identifications can be determined.…”
Section: Noteworthy Observationsmentioning
confidence: 99%
“…A number of species in the genus Corallium have recently been transferred to the genus Hemicorallium (encompassing species discussed here; Cordeiro et al 2019); this is based on the work of Tu et al (2015a, b, 2016). Species in the genus Hemicorallium are represented in the SBMNH collection by a single specimen, SBMNH 471940 (likely Hemicoralliumducale ; see Appendix 1: List of material examined), but three species have been recorded (collected west of the California Channel Islands), in proximity to the western boundary edge of the Bight (location data for specimens housed at NMNH).…”
Section: Systematic Accountsmentioning
confidence: 99%
“…The work by Tu et al (2015a, b; 2016) resulted in most species of Corallium being placed in the genus Hemicorallium . WoRMS (Cordeiro et al 2019) confirms the placement of the species discussed here: H.ducale , H.imperiale , H.regale (as well as H.laauense ); all are listed as accepted, separate species.…”
Section: Systematic Accountsmentioning
confidence: 99%
“…Tu et al (2015b) revised the three genera of Coralliidae: Corallium (having strong longitudinally grooved axes with pits usually raindrop-shaped especially near branch tips), Hemicorallium (having tentacles with long rod sclerites, cylindrical autozooid mounds and smooth axes) and Pleurocorallium (having hemispherical autozooid mounds and axes without raindrop-shaped pits). Recently, Tu et al (2016) described one new species from Hawaii and four from New Caledonia, and suggested Pleurocorallium kishinouyei (Bayer, 1996) was a junior synonym of P. porcellanum. They concluded that there were 7 species in the genus Corallium, 18 species in Hemicorallium and 17 species in Pleurocorallium, for a total of 42 species in the family Coralliidae (Tu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tu et al (2016) described one new species from Hawaii and four from New Caledonia, and suggested Pleurocorallium kishinouyei (Bayer, 1996) was a junior synonym of P. porcellanum. They concluded that there were 7 species in the genus Corallium, 18 species in Hemicorallium and 17 species in Pleurocorallium, for a total of 42 species in the family Coralliidae (Tu et al 2016).…”
Section: Introductionmentioning
confidence: 99%